Single cell immune profiling in ankylosing spondylitis reveals resistance of CD8+ T cells to immune exhaustion - Michael Tang; Zoya Qaiyum; Melissa Lim; Robert D. Inman (iScience)
Summary: Persistent chronic inflammation is a hallmark of ankylosing spondylitis (AS), with cytotoxic T cells (CTLs) increasingly implicated in its pathogenesis. Ordinarily, T cell exhaustion follows sustained, persistent T cell activation to limit collateral tissue damage. Using mass cytometry and single-cell RNA sequencing (scRNA-seq), we identified a clonally expanded CTL subset in AS synovial fluid that expresses inhibitory receptors (PD-1, TIGIT, LAG-3) yet retains its effector capacity to express granzymes, perforin, TNF-α, and IFN-γ. Gene expression profile of this CTL subset shows the downregulation of canonical exhaustion markers. At the protein level, TOX, a critical transcription factor regulating CTL exhaustion, is downregulated in PD-1+TIGIT+LAG-3+CTLs. In-silico trajectory analyses suggest that these cells may differentiate into other effector CTL subsets. Our findings reveal a checkpoint-expressing CTL population in AS that resists exhaustion and retains an activated, effector phenotype. We propose that failure to undergo exhaustion may be a fundamental mechanism sustaining AS chronic inflammation.